The NFκB Signaling Pathway Is Involved in the Pathophysiological Process of Preeclampsia - Li, Yaxi; Zhu, Qinying; He, Ruifen; Du, Junhong; Qin, Xue; Li, Yi; Liang, Xiaolei; Wang, Jing (Geburtshilfe und Frauenheilkunde, 2024)
The high prevalence of preeclampsia (PE) is a major cause of maternal and fetal mortality and affects the long-term prognosis of both mother and baby. Termination of pregnancy is currently the only effective treatment for PE, so there is an urgent need for research into its pathogenesis and the development of new therapeutic approaches. The NFκB family of transcription factors has an essential role in inflammation and innate immunity. In this review, we summarize the role of NFκB in normal and preeclampsia pregnancies, the role of NFκB in existing treatment strategies, and potential NFκB treatment strategies.
Keywords: inflammation; NFκB; preeclampsia (PE); pregnancy; treatment